Deadly harvest - Walker, Carolyn (Cambridge English readers. Level 6, 1999)
Jane Honeywell is a city detective in a sleepy country town who wonders why she's moved there. But then the rural peace is suddenly disturbed by a particularly horrible murder and Jane starts the dangerous pursuit of the killer or killers.